Establishment, Functioning, Challenges, and One-Year Report of Uttar Pradesh’s First Apex Trauma Center - Gunjiganvi, Mallikarjun; Rai, Siddharth; Awale, Rupali; Agarwal, Amit (Indian Journal of Neurotrauma, 2019)
Trauma is a major public health problem across the world with significant morbidity and mortality. Broadly, it is a disease of middle-aged population and is assuming the status of an epidemic in the 21st century. Road traffic injuries are most common followed by railway injuries, industrial, farming, and domestic injuries, and many others in low- and middle-income countries. Severe traumatic brain injuries are the major proportion with concern for long-term cognitive impairment and high spinal cord injuries due to complete dependence. There is no comprehensive trauma care system covering all geography in India at present. The Government of India (GOI), in 2006, established Jai Prakash Narayan Apex Trauma Center, which is run by All India Institute of Medical Sciences at New Delhi as an apex center to provide quality care, training, research, and registry development. It acts as a role model center for the establishment of new centers and helps in upgradation of existing hospitals to provide quality care trauma services. To curb this epidemic of trauma, GOI envisioned National Trauma Care program during the 11th and 12th Five-Year Plans to strengthen the emergency facilities in government hospitals. Many new centers are coming up with various levels of trauma care across the country. Here we discuss the establishment, resources, initial challenges, trauma burden, and a year of report card of the Uttar Pradesh’s first Level I Apex Trauma Center of Sanjay Gandhi Postgraduate Institute of Medical Sciences, Lucknow, established with a vision of providing state of the art Level I trauma care to the injured victims.
Keywords: Apex Trauma Center; trauma; trauma epidemic; trauma system; trauma systems in India